To solve the equation 3x + 2 = 6, we will isolate the variable x by following these steps:
- First, we need to eliminate the constant term on the left side of the equation. We can do this by subtracting 2 from both sides:
3x + 2 – 2 = 6 – 2
This simplifies to:
3x = 4
- Next, we need to solve for x by dividing both sides of the equation by 3:
x = 4 / 3
So, the solution to the equation 3x + 2 = 6 is x = 4/3. This means that if you substitute 4/3 back into the original equation, both sides will be equal, verifying that our solution is correct.